Pemanfaatan New Media dalam Promosi Perhotelan di Kota Bengkulu - Kukuh Bagus Suryo Waskito; Eceh Trisna Ayuh (JOPPAS: Journal of Public Policy and Administration Silampari, 2020)
The purpose of this study is to focus on how the new media is used as a promotional tool for hotels in the city of Bengkulu. This research method uses qualitative methods and Innovation Diffusion theory models. The results of this study are that the study of 4 elements of the theory of innovation diffusion (innovation, time period, communication and social channels) has a relationship with the use of new media at this time. Conclusion, Like the selection of innovations that have an impact in the current era, the time period chosen to decide why should promote through new media, communication channels that have their own influences such as a wide range of promotions, to social that makes changes to the emergence of the use of new media as a promotion from the hotel in the city of Bengkulu. Keywords: Promotion Media, New Media, Promotion